Penajaman Peran Penganggaran Sektor Publik Sebagai Alat Perencanaan Dan Pengendalian - Ali Tafriji Biswan; Defian Panji Ponco Kusumo (JAS (Jurnal Akuntansi Syariah), 2021)
This study aims to examine the non-tax state revenue (NTSR) budgeting process at the Pesi Resort Police (object name be camouflaged). This study is a qualitative one with a comparative approach comparing the Resort Police's Budget Realization Report with the budgeting regulations. To meet the research objectives, conducted and processed data through literature studies and interviews. The study results found that most of the 96 percent NTSR came from services to the community in accordance with the duties and functions of the Resort Police. In general, the research object has fulfilled the budgeting process. However, it has not been carried out more carefully in terms of planning for NTSR revenue budget items. The realization of the NTSR target reaches 2,000 percent, considering that many revenue accounts are not budgeted. The study suggests that the study object should make a more detailed budget planning for each NTSR revenue budget item so that each item is more realistic so that it supports the use of NTSR funds to improve services according to budget as a planning controlling tool.